HUBUNGAN PENGETAHUAN EVALUASI DAN SUPERVISI PENGAWAS DENGAN KINERJA EVALUASI GURU PENDIDIKAN AGAMA ISLAM (PAI) DI SD KABUPATEN TANAH DATAR - ROMI MAIMORI (Ta'dib, 2014)
The problem of this reseach was the lack of the teachers’ knowledge and understanding about the evaluation of students’ achievement. This research was descriptive research (correlation research). The population of this research was all Islamic elementary school teachers at Tanah Datar regency. They are about 319 teachers. The sample of this research was 98 teachers. The sample was selected by using stratified propotional random sampling technique that is through cohcran technique. The instrument of this research was questionnaire (Linkert scale). The evaluation of students’ achievement was variable Y, and supervisors’ supervision was variable X2. And, the teachers’ knowledge of evaluation (variable X1) was analyzed by using objective test.The result of the research showed that: 1) there is any correlation between the teachers’ understanding of avaluation to the teachers’ achievement of evaluation of Islamic teachers at elemeantary schools at Tanah Datar regency, 2) there is any correlation between the supervisors’ supervision to the teachers’ achievement of evaluation of Islamic teachers at elemeantary schools at Tanah Datar regency, 3) the teachers’ anderstanding and their supervision of evaluation influenced the teachers’ achievement of evaluation of Islamic teachers at elemeantary schools at Tanah Datar regency.Kata kunci: pengetahuan evaluasi, supervisi pengawas, kinerja evaluasi guru